Место памятников сабатиновского типа в структуре культурного комплекса Кукутень-Триполье - Бурдо, Н.Б. (Материалы по археологии Северного Причерноморья, 2015)
Памятники сабатиновского типа были выделены в начале 80-х годов Е.К. Черныш на основании анализа материалов двух поселений на Южном Буге – Сабатиновка I и Березовская ГЭС. Поселения, о которых пойдет речь в настоящей статье, локализуются по обоим берегам Южного Буга в Одесской и Кировоградской областях. Основной фонд источников по этим памятникам находится в Одесском археологическом музее НАНУ. В последние десятилетия появились новые данные, позволяющие охарактеризовать группу поселений Триполья ВI на Южном Буге, относящихся к сабатиновскому типу. Sabatynivka-type sites are not numerous and located at the Southern part of South Bug flow. They existed here near 200 years (~ from 4700 to 4500 BC). Last years few new sites by local specialists were discovered, and total amount of sites increased up to 8. Only two of them were explored by archaeologists. Berezivska GES (Berezivka) is the largest (near 10 ha square), and pollibly was a central place of this group. Here were investigated 3 horizons of occupation, which included burnt houses, pits with remains of burnt houses, pits with numerous finds of pottery, figurines, flint tools and animal bones. Painted pottery, found at Berezivska GES, came from Subcarpathian Moldova; other finds have parallels with Gumelnitsa culture. These contacts guaranteed the prosperity of local communities. Richness of finds, which included copper objects, contracts with poorness of the Borysivka group sites, located far to North. Disappearance of Sabatynivka group correlated with climate changes and collapse of Gumelnitsa cultural complex. At the same time Northern groups of trypillians, which supported contacts with Carpathian region, flourished and lated occupied large areas between Southern Bug and Dnieper, where at Trypillia BI-BII stage appeared mega-sites, such as Onoprievka, Vesely Kut and Trypillia.